Deep brain stimulation of the subthalamic nucleus affects resting EEG and visual evoked potentials in Parkinson's disease - Jech, Robert; Růzicka, Evzen; Urgosík, Dusan; Serranová, Tereza; Volfová, Markéta; Nováková, Olga; Roth, Jan; Dusek, Petr; Mecír, Petr (Clinical neurophysiology, 2006)
OBJECTIVE: We studied changes of the EEG spectral power induced by deep brain stimulation (DBS) of the subthalamic nucleus (STN) in patients with Parkinson's disease (PD). Also analyzed were changes of visual evoked potentials (VEP) with DBS on and off. METHODS: Eleven patients with advanced PD treated with bilateral DBS STN were examined after an overnight withdrawal of L-DOPA and 2 h after switching off the neurostimulators. All underwent clinical examination followed by resting EEG and VEP recordings, a procedure repeated after DBS STN was switched on. RESULTS: With DBS switched on, the dominant EEG frequency increased from 9.44+/-1.3 to 9.71+/-1.3 Hz (P<0.01) while its relative spectral power dropped by 11% on average (P<0.05). Switching on the neurostimulators caused a decrease in the N70/P100 amplitude of the VEP (P<0.01), which inversely correlated with the intensity of DBS (black-and-white pattern: P<0.01; color pattern: P<0.05). CONCLUSIONS: Despite artifacts generated by neurostimulators, the VEP and resting EEG were suitable for the detection of effects related to DBS STN. The acceleration of dominant frequency in the alpha band may be evidence of DBS STN influence on speeding up of intracortical oscillations. The spectral power decrease, seen mainly in the fronto-central region, might reflect a desynchronization in the premotor and motor circuits, though no movement was executed. Similarly, desynchronization of the cortical activity recorded posteriorly may by responsible for the VEP amplitude decrease implying DBS STN-related influence even on the visual system. SIGNIFICANCE: Changes in idling EEG activity observed diffusely over scalp together with involvement of the VEP suggest that the effects of DBS STN reach far beyond the motor system influencing the basic mechanisms of rhythmic cortical oscillations.
Keywords: reakční čas; Evoked Potentials, Visual; mapování mozku; hluboká mozková stimulace; Analysis of Variance; Electroencephalography; zrakové evokované potenciály; Male; Subthalamic Nucleus; elektroencefalografie; Reaction Time; Aged; Deep Brain Stimulation; mužské pohlaví; senioři; Dose-Response Relationship, Radiation; Brain Mapping; lidé; ženské pohlaví; analýza rozptylu; Humans; nucleus subthalamicus; vztah dávky záření a odpovědi; Female; Parkinson Disease; Parkinsonova nemoc; lidé středního věku; Middle Aged